1980
DOI: 10.1016/0368-1874(80)80408-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical formation and reduction of silver oxides in alkaline media

Abstract: The anodic oxidation of silver electrodes in NaOH solution and the reduction of the silver oxides formed were studied by potential step chronoamperometry. Oxidation of Ag to Ag20 is a diffusion-controlled reaction, the diffusion control being established in the solid phase. Oxidation of Ag20 to AgO proceeds via a nucleation and growth-controlled process. The amount of AgO decreased with increasing step height. The current--time curves for this reaction have been analysed with the Kolmogoroff--Avrami equation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
1
7
0
5
Order By: Relevance
“…[14,15] The mechanism and the kinetics of Ag(I)-to Ag(II)-oxide formation as well as the morphology of the grown Ag(II) deposits were recently investigated in detail, and the results show that silver(II) oxide formation proceeds via nucleation, 3D growth and Ostwald ripening processes, [16] which was confirmed by previous studies based mainly on electrochemical experiments (e.g. refs [1,17]). Although there is general agreement about the formation of primary and secondary Ag(I) oxides and AgO with increasing oxidation potential, there is still a lack of detailed structural information during the different growth stages of the anodic oxides.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…[14,15] The mechanism and the kinetics of Ag(I)-to Ag(II)-oxide formation as well as the morphology of the grown Ag(II) deposits were recently investigated in detail, and the results show that silver(II) oxide formation proceeds via nucleation, 3D growth and Ostwald ripening processes, [16] which was confirmed by previous studies based mainly on electrochemical experiments (e.g. refs [1,17]). Although there is general agreement about the formation of primary and secondary Ag(I) oxides and AgO with increasing oxidation potential, there is still a lack of detailed structural information during the different growth stages of the anodic oxides.…”
Section: Introductionsupporting
confidence: 74%
“…In most of the cases, the silver electrodes were then preoxidized at a potential of +0.7 V(SHE) for 600 s. Under these electrochemical conditions, a thick, crystalline Ag 2 O film was formed, [1,2,7,8] and the AgO formation was subsequently initiated by a second potential step to more anodic potentials. Finally, the samples were removed from the solution under potential control and rinsed with distilled water to remove any remaining electrolyte.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Согласно литературным данным [28,29], два небольших максимума (А 1 , А 2 ) на анодных ветвях циклических зависимостей 1'-3′ соответствуют процессам окисления серебра из состава наночастиц. Схемы реакций их окисления (1), (2) согласуются с [27,[29][30][31]:…”
Section: результаты экспериментаunclassified
“…However, in the cathodic scan, there is an anodic peak at about 450 mV, which is attributed to the further oxidation of silver(I). Droog and Huisman concluded that the formation of Ag 2 O occurs by a diffusion process while the formation of AgO occurs by a nucleation and growth process [17]. Once nucleation has occurred, further oxidation can proceed at a lower potential.…”
Section: Introductionmentioning
confidence: 99%